2020
DOI: 10.22271/chemi.2020.v8.i4e.10034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of egg albumen (egg white) fortified mulberry leaf on rearing and some cocoon parameters of silkworm, Bombyx mori L. (CSR6 × CSR26) × (CSR2 × CSR27) double hybrid

Abstract: Fortification of mulberry leaf with egg albumen and its impact on commercial characteristics of Silkworm (Bombyx mori L.) was conducted at College of Temperate Sericulture Mirgund SKUAST-K during spring 2017. The silkworm double hybrid (CSR6 × CSR26) × (CSR2 × CSR27) was reared on mulberry leaves fortified with aqueous egg albumen solution daily once during fourth and fifth instar. Four different concentrations of egg albumen viz., 5%, 10%, 15% and 20% were tested. Egg albumen improved all the rearing and coco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…In our study, the larval weights as well as the percentage ratio of silk gland weight to the body weight of larvae fed with amino acid fortified mulberry leaves were significantly higher as compared to larvae of the control group at day 1–7 of 5th instar. A similar increase in larval weight and silk gland weight was also reported in silkworm larvae when they were fed with mulberry leaves supplemented with raw whey protein, royal jelly and egg white [ 37 , 44 ]. The highest weight of larvae was recorded in silkworms fed with 1 % alanine coated mulberry leaves.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our study, the larval weights as well as the percentage ratio of silk gland weight to the body weight of larvae fed with amino acid fortified mulberry leaves were significantly higher as compared to larvae of the control group at day 1–7 of 5th instar. A similar increase in larval weight and silk gland weight was also reported in silkworm larvae when they were fed with mulberry leaves supplemented with raw whey protein, royal jelly and egg white [ 37 , 44 ]. The highest weight of larvae was recorded in silkworms fed with 1 % alanine coated mulberry leaves.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, the commercial and biological traits of B. mori were observed after feeding them with amino acids fortified mulberry leaves. The silkworms have an equal tendency to consume both the fortified and non-fortified mulberry leaves [ 37 ]. Our study showed that the silkworm larvae fed with mulberry leaves supplemented with amino acids showed a significant improvement in both biological and commercial traits as compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Bombyx mori, utilizes all amino acids in Egg albumen especially the essentials during the growth and development to synthesis silk fiber Islam et al (2020). Due to its technological properties antimicrobial and antiviral activity egg white protein used as a raw material for the food and pharmaceutical industries Kovacs-Nolan et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Intake of food and production of silk in silkworms are very closely associated to nutritional factors. Influence of mulberry nutrition and feeding of egg albumen treated mulberry leaves has been found to have profound effect on the growth and development of silkworm larva (Islam et al, 2020a(Islam et al, , 2020b. Dietary efficiency in silkworms plays a key role for converting the consumed mulberry leaves to silk thread.…”
Section: Introductionmentioning
confidence: 99%